Identification of potential human oncogenes by mapping the common viral integration sites in avian nephroblastoma - Pajer, Petr; Pecenka, Vladimír; Králová, Jarmila; Karafiát, Vít; Průková, Dana; Zemanová, Zdena; Kodet, Roman; Dvorák, Michal (Cancer research, 2006)
Gene deregulation is a frequent cause of malignant transformation. Alteration of the gene structure and/or expression leading to cellular transformation and tumor growth can be experimentally achieved by insertion of the retroviral genome into the host DNA. Retrovirus-containing host loci found repeatedly in clonal tumors are called common viral integration sites (cVIS). cVIS are located in genes or chromosomal regions whose alterations participate in cellular transformation. Here, we present the chicken model for the identification of oncogenes and tumor suppressor genes in solid tumors by mapping the cVIS. Using the combination of inverse PCR and long terminal repeat-rapid amplification of cDNA ends technique, we have analyzed 93 myeloblastosis-associated virus type 2-induced clonal nephroblastoma tumors in detail, and mapped >500 independent retroviral integration sites. Eighteen genomic loci were hit repeatedly and thus classified as cVIS, five of these genomic loci have previously been shown to be involved in malignant transformation of different human cell types. The expression levels of selected genes and their human orthologues have been assayed in chicken and selected human renal tumor samples, and their possible correlation with tumor development, has been suggested. We have found that genes associated with cVIS are frequently, but not in all cases, deregulated at the mRNA level as a result of proviral integration. Furthermore, the deregulation of their human orthologues has been observed in the samples of human pediatric renal tumors. Thus, the avian nephroblastoma is a valid source of cancer-associated genes. Moreover, the results bring deeper insight into the molecular background of tumorigenesis in distant species.
Keywords: kur domácí; Poultry Diseases; nádory ledvin; polymerázová řetězová reakce; Chromosome Mapping; Proviruses; DNA-Binding Proteins; ptačí proteiny; Chickens; Wilms Tumor; Genes, Tumor Suppressor; Kidney Neoplasms; Oncogene Proteins; Avian Proteins; Avian Myeloblastosis Virus; DNA vazebné proteiny; virus ptačí myeloblastózy; transkripční faktor Twist; nemoci drůbeže; Genes, ras; Virus Integration; Animals; geny ras; lidé; kuřecí embryo; Oncogenes; mapování chromozomů; proviry; onkogenní proteiny; zvířata; onkogeny; Humans; Twist-Related Protein 1; integrace viru; Polymerase Chain Reaction; Terminal Repeat Sequences; Wilmsův nádor; tumor supresorové geny; koncové repetice; Chick Embryo